The personality-oriented approach in the evaluation and management of the flight safety conditions - B. I. Bachkalo; V. I. Zolotykh (Научный вестник МГТУ ГА, 2019)
The causes of most accidents are due to the manifestations of the personal factor of the flight crew during flight operations. In view of this, the question arises - why do the same well-known dangerous factors, based on the psychophysiological features and limitations inherent in a particular individual piloting the aircraft, continue to affect flight safety in the most negative way. This is explained by the fact that during the entire period of aviation development, the tasks of accidents prevention were solved, and the tasks of the particular flight safety and managing the safety of a particular flight were not given due attention. During the creation of the fundamentals of a modern flight safety system, the primary object of impact is to determine the primary aviation system, the main elements of which are a particular pilot and a particular aircraft on which he performs the flight. With such a prioritization of flight safety issues, the identity of a particular pilot as a central element of a manned aviation system prevails. In this case, it becomes obvious the need for a systematic consideration of the personal qualities of a given pilot, capable of affecting flight safety - what is called the "personal factor" in the language of aviation specialists. The "personal factor" is in fact an integral part of the "human factor", so the real opportunity to control the human factor of the flight crew of aviation units will appear subject to the control of the "personal factor" of each particular pilot. To do this the personality-oriented approach in assessing and managing the state of the aviation system is required.